Komunikasi Vertikal dalam Servant Leadership Kadis Pendidikan dan Kebudayaan Kota Tomohon - Gracia Rachmi Adiarsi; Jeremia Engelita Wakas (Jurnal Komunikasi Global, 2018)
The style of leadership determines the success of vertical communication in the organization. Rigid leadership and protocols are familiar to leaders and government officials. This study aims to find out and understand the application of vertical communication in the style of servant leadership from the Head of Education and Culture Bureau, Tomohon. This study used a qualitative approach with data collection techniques through in-depth interviews with six informants selected by purposive sampling technique. The results showed that vertical communication performed by the Head of Office in Tomohon demonstrated a service leadership style including ten servant leadership characteristics that made the vertical communication more effective. The ten characteristics of leadership that were listening, empathy, healing, awareness, persuasion, conceptualization, foresight, stewardship, commitment to community growth and community building.